Effects of atorvastatin on human C-reactive protein metabolism - Thongtang, Nuntakorn; Diffenderfer, Margaret R.; Ooi, Esther M.M.; Asztalos, Bela F.; Dolnikowski, Gregory G.; Lamon-Fava, Stefania; Schaefer, Ernst J. (Atherosclerosis, 2013)
Statins are known to reduce plasma C-reactive protein (CRP) concentrations. Our goal was to define the mechanisms by which CRP was reduced by maximal dose atorvastatin. Eight subjects with combined hyperlipidemia (5 men and 3 postmenopausal women) were enrolled in a randomized, placebo-controlled double-blind, cross over study. Subjects underwent a 15-h primed-constant infusion with deuterated leucine after 8 weeks of placebo and 80 mg/day of atorvastatin. CRP was isolated from lipoprotein deficient plasma, (density > 1.21 g/ml) by affinity chromatography. Isotopic enrichment was determined by gas chromatography/mass spectrometry. Kinetic parameters were determined using compartmental modeling. Paired t test and Wilcoxon signed ranks test were used to compare differences between placebo and atorvastatin. Compared with placebo, atorvastatin decreased median CRP pool size by 28.4% (13.31 ± 3.78 vs 10.26 ± 3.93 mg; p = 0.16), associated with a median CRP fractional catabolic rate increase of 39.9% (0.34 ± 0.06 vs 0.50 ± 0.11 pools/day; p = 0.09), with no significant effect on median CRP production rate (0.050 ± 0.01 vs 0.049 ± 0.01 mg/kg/day; p = 0.78). Our data indicate that maximal doses of atorvastatin lower plasma CRP levels by substantially decreasing the median CRP plasma residence time from 2.94 days to 2.0 days, with no significant effect on the median CRP production rate. ► Statins are known to reduce plasma C-reactive protein (CRP) concentrations. ► We aim to define the effects of atorvastatin 80 mg/day vs placebo on CRP kinetics. ► Atorvastatin lower plasma CRP levels by substantially increasing CRP catabolism. ► There was no significant effect of atorvastatin on CRP production rate.